The reliability of laboratory performance testing - Schabort, Elske Jeanne (MRC/UCT RU for Exercise and Sport Medicine, 2017)
The reproducibility of a measurement in a laboratory test impacts on the power of that test to detect the small, but significant changes in an athlete's performance when determining the influence of a new training or nutritional intervention. Until recently, however, sport scientists have not been concerned with establishing the reliability of many of their testing protocols. Therefore, the purpose of this thesis was to examine the reliability of several laboratory tests of performance and to determine those factors which may impact on the reproducibility of those tests. Possible factors that could contribute to the reliability of a performance test include the type of exercise protocol employed (continuous, intermittent), the equipment on which the subject performs the test, the intensity and duration of the testing protocol, the subject's state of fitness and whether he is familiar with the testing conditions.